Improving Leadership Behavior to Influence a Better Employee Performance Case Study Aryaduta Hotel Bandung - Ramadhian, Mochamad Arief Rahman; Welly, John (LPPM-STPI, 2022)
Hotel Aryaduta Bandung established since February 1, 2016 which has been managed by Hyatt Regency, the hotel is under the company Lippo Karawaci is located on Jl.Sumatra No.51 Bandung, with a land area of 7000m2 of 42000m2 with 17 floors and 2 basement and has 245 this hotel even though the hotel building has been established since 1997. Aryaduta Bandung Hotel provides excellent service and facilities, from 245 rooms equipped with a calm and harmonious atmosphere, the hotel offers the best facilities. Based on interview with several employees, to provide excellent service, the function of a leader must be significant. Because a leader can direct and also guide his subordinates in order to provide the best service. But this hasn't happened yet, because the leader doesn't have leadership skills to increase porosity in his / her department. Not to mention a leader must have a good relationship with his subordinates to create an atmosphere that can increase job satisfaction. To increase productivity and excellent service, Aryaduta Bandung Hotels must improve the existing leadership behavior. For this study using the Leadership Practices Inventory. LPI is a questionnaire that measures leadership behavior, developed by Kouzes and Posner. This LPI contains 30 items aimed at measuring the five dimensions of transformational leadership from the leadership model proposed by Kouzes and Posner, challenging the process, inspiring a shared vision, enabling others to act, the way model, and encourage the heart.